CGIAR submission on the draft action plan for the implementation of the capacity development strategy of the international treaty 2023-2030 - CGIAR Genebank Accelerator (2025)
Submitted in response to Notification NCP GB11-11. This submission is divided in two parts: The first part includes comments and suggestions on the Draft Action Plan for the Capacity Development Strategy of the International Treaty 2023-2030. The second part provides an overview of relevant CGIAR capacity development plans in its 2025-2030 Research Portfolio, focusing on particularly relevant activities of the Capacity Sharing for Development Accelerator, Genebanks Accelerator, and Breeding for Tomorrow Programme. By sharing this information, we aim to facilitate coordinated efforts and synergies among the International Treaty’s Capacity Development Strategy and the CGIAR capacity sharing plans.